Erectile dysfunction treatment with combination of mesenchymal stem cell derived exosomes and focused low-intensive shock wave therapy - Zasieda, Y. I.; Засєда, Юрій Ігорович (My University, 2020)
Relevance. Erectile dysfunction brings basic problem of urology, andrology and sexology. Erectile dysfunction have significant impact on quality of life, sexual and reproductive health and psychological condition in men. Novel experimental and clinical studies a several methods of regenerative medicine shoved simultaneous impact on main pathogenetic aims showing significant levels of clinical efficacy. Aim – to develop and analyze clinical effects of mesenchymal stem cell-derived exosomes intracavernous injections and low-intensity extracorporeal shock-wave therapy combination in patients with severe erectile dysfunction on background of metabolic syndrome and atherosclerosis. Materials and methods. A prospective clinical study was conducted on a contingent of 38 patients of “Men’s Health +” Clinic” (Kyiv, Ukraine) suffering from severe organic erectile dysfunction (ICD-10:N52.9; International index of erectile function score lower than 7) on the background of metabolic syndrome (ICD-10: E88.81) and generalized atherosclerosis (ICD-10: I70.9). Study results. Therapeutics model of combined application of mesenchymal stem cell-derived exosomes intracavernous injections and low-intensity extracorporeal shock-wave therapy showed significant positive impact of applied therapeutic model according to IIEF-5, EHS scores as well as due to pharmacodoppler-sonography data. Therapeutics model of application low-intensity extracorporeal shock-wave therapy also showed significant positive impact on same diagnostic categories. Conclusion. Comparison of post-therapeutic data between MG and CG showed absence of significant differences in all categories besides mean PSV, but values of statistical mistake probability are very close to significance threshold for IIEF-5 severe and moderate categories as well as EHS grades 4 and 2, what highlights perspective of further comparison studies on larger population scales, longer observation periods or less severe forms of ED. Актуальність. Еректильна дисфункція створює базові проблеми урології, андрології та сексології. Еректильна дисфункція значно впливає на якість життя, сексуальне і репродуктивне здоров’я та психологічний стан чоловіків. Нові експериментальні і клінічні дослідження методів регенеративної медицини виявили потенціал впливу даних методів на основні патогенетичні цілі, демонструючи значний рівень клінічної ефективності. Мета – розробити і проаналізувати клінічні ефекти комбінації інтракавернозних ін’єкцій екзосом мезенхімальних стовбурових клітин і низькоінтенсивної екстракорпоральної ударно-хвильової терапії у пацієнтів з важкою еректильною дисфункцією на фоні метаболічного синдрому і атеросклерозу. Матеріали та методи. Проспективне клінічне дослідження було проведено на контингенті з 38 пацієнтів «Клиники «Мужское здоровье+» (Київ, Україна), із тяжкою формою органічної еректильної дисфункції (МКХ- 10: N52.9; Міжнародний індекс еректильної функції менше 7 балів) на тлі метаболічного синдрому ( МКХ-10: E88.81) і генералізованого атеросклерозу (МКХ-10: I70.9).
Лікування еректильної дисфункції комбінацією екзосом, отриманих з мезенхімальних стовбурових клітин і низькоінтенсивною ударно-хвильовою терапією
Keywords: regenerative medicine; erectile dysfunction; metabolic syndrome; exosomes; low-intensity extracorporeal shock-wave therapy; регенеративна медицина; еректильна дисфункція; метаболічний синдром; екзосома; низькоінтенсивна екстракорпоральна ударно-хвильова терапія